Pengolahan Hasil Pertanian Nilai Tambah Ekonomi Kepada Mahasiswa Pertanian - Mahrus Ali; Yeni Ika Pratiwi; Sutriyono; Nanang Sutomo; Sukijo; Soiman (Universitas Merdeka Surabaya, 2020)
The real realization of support from universities is to provide entrepreneurial knowledge. Not only in theory but also in application. Thus students will get real experience and understand the ins and outs of the business world. This experience can later be used to help small and medium entrepreneurs in managing and developing their businesses. Students can also help by continuing to buy domestic products, so that MSME actors can continue to survive and develop. In addition, it is also hoped that business actors can become more motivated and open to creative ideas, by sharing entrepreneurship tips from agricultural products, maintaining quality and so on.